Scavenging capacity of strawberry tree (Arbutus unedo L.) leaves on free radicals - Oliveira, Ivo (2011)
Despite strawberry tree (Arbutus unedo L.) leaves had a long use in traditional medicine due to its antiseptic, diuretic, astringent and depurative properties, the potential of their antioxidant activity are still lacking. Our study goals to assess the antioxidant and free radical scavenging potential of water, ethanol, methanol and diethyl ether extracts of A. unedo leaves. Total phenols content was achieved spectrophotometrically using Folin–Ciocalteau reagent with gallic acid as standard. Antioxidant activity was evaluated using three different methods: reducing power of iron (III)/ferricyanide complex assay, scavenging effect on DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and scavenging effect on superoxide radicals by using the PMS–NADH–nitroblue tetrazolium system. Ethanol extracts of A. unedo leaves were the highest in reducing power (IC50 232.7 lg/mL) and DPPH scavenging effect (IC50 63.2 lg/mL) followed by water extracts (with IC50 of 287.7 and 73.7 lg/mL, respectively); whereas diethyl ether extracts were the lowest. In the scavenging on superoxide radical assay, methanol extracts obtained the best results (IC50 6.9 lg/mL). For all the methods tested the antioxidant activity was concentration dependent. In accordance with antioxidant activity, highest total phenols content were found in ethanol, followed by water, methanol and diethyl ether extract. The results indicated that A. unedo leaves are a potential source of natural antioxidants.